Thinking “We” in Brome’s Antipodes - Lyne, Raphael (Early Theatre)

(untitled) (McMaster University Library Press / Becker Associates, 2026)
This essay investigates the first person plural perspective, “we,” in Richard Brome’s Antipodes (ca 1636). The discovered intimacy, cooperative action, ingenious improvisation, and occasional chaos seen in the play generate acute representations of emergent common purpose and experience. Comparing Brome’s treatments and attitudes with those in other works, especially Francis Beaumont’s Knight of the Burning Pestle (1607), the essay places these elements of the Antipodes in their theatrical environment, reveals how they are challenged by modern scholarship contesting assumptions about mutuality, and illuminates them with reference to philosophical and psychological attempts to pin down the place of “we”-experience in the individual.